Peran Badan Penyelenggara Jaminan Produk Halal (BPJPH) terhadap Konsumen Dihubungkan dengan Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen: (Studi Kasus : Sembilan Produk Makanan Mengandung Unsur Babi (Porcine) Tanpa Label yang Jelas) - Indah Rahmalia; Yuniar Rahmatiar; Muhamad Abas (Jurnal Hukum Lex Generalis, 2025)
The discovery of nine children's food products containing pork (porcine) by BPJPH and BPOM in April 2025 raised public concern, especially since seven of them had halal certification. This study examines the role of BPJPH in protecting consumer rights under Law Number 8 of 1999, focusing on cases of ingredient falsification. Using a normative juridical approach and case study method, the findings reveal weak post-market surveillance by related agencies, resulting in significant spiritual and material losses for Muslim consumers. The study highlights the urgent need for more effective preventive, repressive, and coordinative measures to uphold consumer protection and halal assurance.